The Exploration of People, Price, Place, dan Promotional Techniques on Parents' Decision to Enroll Globe National Plus Batam School: Findings from Explanatory Sequential Design - Andi Zamudra; T Tibrani; Lukmanul Hakim (CV. Media Digital Publikasi Indonesia, 2026)
Private educational institutions, particularly private schools, contribute significantly to effective learning processes and produce graduates meeting user standards through their sustainability and development. The input aspect is empirically the most crucial for the effectiveness of a school's process and output. To achieve a balanced input, schools must offer diverse programs and promotional systems to attract parents to enroll their children. This study investigates how people, price, place, and promotional strategies influence parents' decisions to select Globe National Plus Batam School for their children's education. It also examines the combined effect of these variables on parental choices. To accomplish these research objectives, a mixed-method approach with an Explanatory Sequential Design was employed. Quantitative data was collected through questionnaires from 250 parents, selected using random sampling. Qualitative data was gathered through closed interviews. The research data underwent stages of collection, reduction, presentation, verification, and conclusion. Multiple linear regression and statistical hypothesis testing were used for data analysis. The study's findings reveal that people, price, place, and promotion significantly impact parents' decisions. These results provide valuable insights for private schools to maintain their competitiveness against public schools in Batam City when recruiting new students. By confirming that input people, price, place, promotion significantly predicts parents’ decisions, the research reinforces the importance of input factors as foundational elements for effective school processes and outcomes, supporting and enriching the input‑process‑output paradigm in educational management literature. Furthermore, this research lays the groundwork for future studies to explore potential reciprocal relationships among the independent variables and identify other factors that may have a stronger influence on parents' decisions to enroll their children at Globe National Plus School Batam.